LEGAL PROTECTION OF PRIVACY DATA THROUGH ENCRYPTION TECHNOLOGY - Thania Christy Corne (Lampung Journal of International Law, 2019)
Technological developments in the era of globalization bring humans into the digital age. All things will directly contact with an electronic system. And so with the data, some of the data among this world is privacy. That’s why encryption is needed to be applied. Initially, encryption was used as a privacy data protector, but in its development encryption gave birth to problems in the legal field. Where criminals use encryption as a shield for their crimes. Therefore, legal issues arise, whether for reasons of government or state security can have access to one’s privacy data. How does international or national law regulate the issue of using decryption of encryption technology? The method used in this paper is a juridical-normative comparative legal research method.The result shows that international law does not regulate the use of encryption in protecting privacy data in the digital world comprehensively because some of the countries claim that the use of encryption is a part of human right, on the other hands some country has another vision on national security.